Evaluating Accessibility and Equity of Multi-Level Urban Public Sports Facilities at the Residential Neighborhood Scale - Wenchao Wang; Yujun Cai; Xiangrui Xiong; Genyu Xu (Buildings)
Accurately assessing the accessibility and equity of urban public sports facilities is essential for improving public service provision and enhancing residents’ well-being. However, most existing studies rely on administrative units such as subdistricts and communities, often overlooking the multi-level structure of such facilities and failing to reflect their distribution within the spatial scope of residents’ daily activities. To address this gap, this study adopted the residential neighborhood as the basic unit of analysis and developed an integrated methodological framework combining the average nearest neighbor index, kernel density estimation, a Gaussian-based two-step floating catchment area method, the Gini coefficient, and location quotient analysis. When applied to Shanghai, the framework revealed distinct spatial patterns across facility levels, exhibiting scale-dependent characteristics. Community-level and residential-level sports facilities were found to be relatively accessible, whereas city-level and subdistrict-level sports facilities showed limited accessibility, particularly in peripheral suburbs. All facility levels exhibited varying degrees of spatial inequality, highlighting persistent issues of spatial justice. These findings provide empirical evidence to inform the spatial optimization of public sports facilities and to promote more equitable access to urban public services.